Preprocedural computed tomography angiography-guided transcatheter arterial embolization for managing esophageal cancer bleeding: a case series study - Yang, Xue-Jiao; Wu, Yong-Juan; Wang, Jing-Zhong; Zheng, Yu-Lan; Cheng, Guang-Yuan; Cui, Yun-Hua; Li, Xiao-Qi (Frontiers in Oncology, 2025)
ObjectiveWhile endoscopy is the first-line treatment for non-variceal upper gastrointestinal hemorrhage, its role in managing upper gastrointestinal tumor bleeding is limited. This study aims to evaluate the effect of computed tomography angiography (CTA)-guided transcatheter arterial embolization (TAE) in achieving hemostasis for esophageal cancer bleeding.MethodsA retrospective case series was conducted at our hospital, involving eight patients who underwent preprocedural CTA-guided TAE for esophageal cancer bleeding between August 2023 and August 2024.ResultsOf the eight patients (seven males, mean age 67 ± 12.9 years) who underwent CTA-guided TAE for esophageal cancer bleeding, seven achieved both technical and clinical success. One patient failed to achieve embolization due to missed identification of a pseudoaneurysm in the superior thyroid artery, resulting in death from hemorrhage. Two patients experienced mild chest or neck discomfort, which resolved with conservative management. During follow-up, five patients experienced recurrent hemorrhage, with four dying and one successfully treated with a second TAE. One of the remaining two patients died from disease progression, and the other remained recurrence-free for 270 days.ConclusionCTA-guided TAE demonstrates high technical and clinical success rates for achieving hemostasis in esophageal cancer bleeding with mild and manageable complications.